A machine independente wCET predictor for microcontrollers and DSPs - Tavares, Adriano (2001)
This paper describes a method for analyzing and predicting the timing properties of a program fragment. The paper first presents a little language implemented to describe a processor’s architecture and a static WCET estimation method is then presented. The timing analysis starts by compiling a processor’s architecture program followed by the disassembling of the program fragment. The assembler program is then decomposed into basic blocks and a call graph is generated. These data are later used to evaluate the pipeline hazards and cache miss that penalize the real-time performance. Finally, some experimental results of using the developed tool to predict the WCET of code segments with some Intel microcontroller are presented. execution, the desired time will be found by averaging. Even with this approach, if you want an accurate measurement, a number of complications such as, compiler optimizations, operating system distortions, must be solved. Nevertheless, these approaches are unrealistic since they ignore the system interferences and the effects of cache and pipeline, two very important features of some processors that can be used in our hardware architecture. Shaw [1], Puschner [2], and Mok [3], developed some very elaborated methodology for WCET estimation, but none of them takes into account the effects of cache and